Electric Power Conversion - Găiceanu, Marian (IntechOpen, 2019)
The introductory chapter to this book is like traveling in a time machine into past, present, and future of electric power conversion. Archeological discoveries are being transformed into the discoveries of the future. The book is an incursion to electric power conversion through electromechanical power conversion, static power conversion, and applications in the field. Each of the above-mentioned sections analyzes the knowledge gained using the experimental results of valuable research projects. Novice readers will learn how energy is converted adequately and adapted to different consumers. Advanced readers will discover different kinds of modern solutions and tendencies in the field of electric power conversion.